ANALISIS PENGARUH ABU SEKAM PADI (RICE HUSK ASH) SEBAGAI BAHAN TAMBAH TERHADAP UJI KUAT TEKAN BETON - Purnama, Rian; Yakup, Vanita Kesuma Wati; Pratiwi, Dian (Universitas Teknokrat Indonesia, 2024)
Concrete serves as the primary building material within the construction industry. Essentially, it comprises a blend of cement, water, fine aggregate, and coarse aggregate, typically in the form of crushed stone or gravel. The compressive strength of concrete refers to the level of load that leads to the failure of a concrete test specimen under a specific compressive force applied using a Compression Testing Machine. Because of its elevated silica content, rice husk ash possesses the potential to enhance concrete quality. Utilizing rice husk ash is anticipated to enhance concrete's compressive strength while also diminishing reliance on costly cement components In this study, rice husk ash was incorporated as an extra component in the concrete mixture. Various percentages of rice husk ash were employed, including 0%, 20%, 40%, and 60%, each tested with five specimens. The conducted test focused on the compressive strength of concrete, performed after 28 days of concrete curing. The mean compressive strength of concrete at 28 days without any variation stands at 21,674 MPa. Introducing a 20% variation with rice husk ash yields an average compressive strength of 14,032 MPa, while a 40% variation results in 5.32 MPa, and a 60% variation results in 4.24 MPa. The peak average compressive strength occurs with a 20% variation, whereas the lowest average value is observed with a 60% variation. These findings indicate that the concrete's compressive strength falls short of the intended target, as incorporating more rice husk ash leads to a decline in concrete quality